2021
DOI: 10.1101/2021.08.20.457112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PASTA kinase-dependent control of peptidoglycan synthesis via ReoM is required for cell wall stress responses, cytosolic survival, and virulence in Listeria monocytogenes

Abstract: Pathogenic bacteria rely on protein phosphorylation to adapt quickly to stress, including that imposed by the host during infection. Penicillin-binding protein and serine/threonine-associated (PASTA) kinases are signal transduction systems that sense cell wall integrity and modulate multiple facets of bacterial physiology in response to cell envelope stress. The PASTA kinase in the cytosolic pathogen Listeria monocytogenes, PrkA, is required for cell wall stress responses, cytosolic survival, and virulence, ye… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
(111 reference statements)
1
3
0
Order By: Relevance
“…Remarkably, the gpsB mutant was also hypersensitive against ceftriaxone (Fig. 1B), as was reported recently in another L. monocytogenes strain background (48). Furthermore, we also found that the prkAΔC mutant showed a pronounced growth defect at 42°C (Fig.…”
Section: Monocytogenes Mutants In Gpsb and Prka Phenocopy Each Othersupporting
confidence: 90%
“…Remarkably, the gpsB mutant was also hypersensitive against ceftriaxone (Fig. 1B), as was reported recently in another L. monocytogenes strain background (48). Furthermore, we also found that the prkAΔC mutant showed a pronounced growth defect at 42°C (Fig.…”
Section: Monocytogenes Mutants In Gpsb and Prka Phenocopy Each Othersupporting
confidence: 90%
“…We previously showed that prkA , encoding a eukaryotic-like serine/threonine protein kinase important for regulation of PG biosynthesis, is essential in L. monocytogenes EGD-e (58, 86). Among the substrates of this kinase are YvcK ( lmo2473 ) and ReoM ( lmo1503 ), both contributing to PG biosynthesis (58, 8688). The precise role of YvcK is not clear, but the yvcK gene is encoded in the same operon next to whiA (30), herein identified as an essential gene at increased temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we found that the PASTA domains of the essential PrkA kinase can be deleted and that the kinase domain contributes the essential functionality. PrkA regulates PG biosynthesis through phosphorylation of ReoM, a small cytosolic protein that controls proteolytic stability of MurA, the first committed step enzyme in PG biosynthesis, which is essential itself (58, 86, 88). ReoM needs to be phosphorylated to prevent degradation of MurA (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation